Determination of inter-bronchial and subcarinal angles in fetuses of different gestational age and their clinical implication - Anne Dsouza; Vrinda Hari Ankolekar; Aswin Das; Supriya Padmashali; Antony Sylvan Dsouza; Mamatha Hosapatna (Wolters Kluwer Medknow Publications, 2015)
Introduction:The tracheo-bronchial angles in the human fetus are of increasing relevance in perinatal medicine to determine both normal and pathological criteria. The present study was undertaken to calculate the inter-bronchial angle using a novel method by an image analyzer at different gestational ages. Materials and Methods:The present study was carried out using 24 human fetuses in the department of Anatomy, Kasturba Medical College, Manipal. The right and left bronchial, inter-bronchial and subcarinal angles were calculated by using an image analyzer named Image J. Results:The right bronchial angle ranged from 21.99° to 43.96°. The left bronchial angle ranged from 29.48° to 56.21°. The inter-bronchial angle ranged from 60.53° to 100.86°. Student t test was applied to compare the means of bronchial angles between the second and third trimesters which did not show any statistical significance. The subcarinal angle ranged from 41.69° to 74.88° with an average of 61.15 ± 9.73°. Conclusion:The present study analyses the inter-bronchial and subcarinal angles in different GA, the knowledge of which would be essential to understand the developmental changes of the respiratory passages.